2015
DOI: 10.1111/jfpp.12512
|View full text |Cite
|
Sign up to set email alerts
|

Drying Characteristics and Processing Parameters for Microwave-Vacuum Drying of Kiwifruit (A ctinidia deliciosa ) Slices

Abstract: This study experimented on microwave-vacuum (MWV) drying of kiwifruit (Actinidia deliciosa) slices as a way to improve drying productivity and the quality of dried fruit. The effects of microwave power density, sample thickness and vacuum degree on the drying characteristics of kiwifruit slices were studied. The results showed that these three factors had significant effects on the vitamin C and chlorophyll contents and on the rehydration capacity of dried kiwifruit slices, as well as the total drying time. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…This effect allows the driving force for mass transfer with evaporation of water from the materials, leading to a shorter drying time. However, damage to the product from electrical arcing in the oven or local overheating could be seen at higher vacuum levels (Tian et al, ). In the literature, Song, Zhang, Mujumdar, and Fan () investigated the effect of pressure levels on the drying kinetics during vacuum microwave drying at 240 W. They found that the drying time of potato decreased with increasing vacuum level.…”
Section: Resultsmentioning
confidence: 99%
“…This effect allows the driving force for mass transfer with evaporation of water from the materials, leading to a shorter drying time. However, damage to the product from electrical arcing in the oven or local overheating could be seen at higher vacuum levels (Tian et al, ). In the literature, Song, Zhang, Mujumdar, and Fan () investigated the effect of pressure levels on the drying kinetics during vacuum microwave drying at 240 W. They found that the drying time of potato decreased with increasing vacuum level.…”
Section: Resultsmentioning
confidence: 99%
“…Particles extracted from the dried samples were vertically cut into 1-mm-thick slices and coated with gold-palladium. All samples were examined under high vacuum (20 kV) (SCD-005, Baltec, Wetzlar, Germany), and then their microphotographs were taken [Tian et al, 2015].…”
Section: Microstructure Analysismentioning
confidence: 99%
“…In literature, most of the studies conducted on the drying of kiwi fruit includes only the HAD method and investigates the effect of HAD parameters (temperature, air velocity, relative humidity) or the sample properties (thickness, initial moisture content) on product quality (Chin, Siew, & Soon, 2015;Kaya, Aydın, & Kolayli, 2010;Mahjoorian et al, 2017;Mohammadi, Rafiee, Djomeh, & Keyhani, 2008). Ascorbic acid content of dried kiwifruit was determined by some authors (Chin et al, 2015;Kaya et al, 2010;Movagharnejad & Pouya, 2017;Orikasa et al, 2014;Tian et al, 2015). Kaya et al (2010) stated that increasing drying air temperature increased the degradation of vitamin C content of dried kiwifruit.…”
Section: Introductionmentioning
confidence: 99%